Hubungan Morfologi dan Kekuatan Otot Quadriceps Femoris dengan Patellofemoral Pain Syndrome pada Olahragawan - Ni Putu Diah Asyana Putri; I Putu Gde Surya Adhitya; I Gede Eka Juli Prasana; Govinda Vittala (KOLONI, 2026)
Patellofemoral Pain Syndrome is a clinical condition characterized by anterior knee pain that commonly occurs in athletes. The development of PFPS is multifactorial, one of which is weakness of the quadriceps femoris muscle. Specifically, atrophy of the vastus medialis oblique (VMO) muscle may also contribute to knee instability, which is associated with a greater risk of sports-related injuries. This study aimed to determine the relationship between quadriceps femoris muscle morphology, muscle strength, and PFPS in athletes. This study employed a cross-sectional design involving 74 athletes aged 16–22 years selected through purposive sampling. Muscle morphology was assessed by measuring the cross-sectional area (CSA) of the VMO using musculoskeletal ultrasonography. Muscle strength was measured using a hand-held dynamometer, while PFPS was identified using the Kujala Questionnaire. Statistical analysis was performed using Spearman’s rho bivariate test.The results demonstrated a significant positive correlation between VMO CSA morphology and Kujala scores (r = 0.24; p = 0.040), as well as between VMO CSA morphology and quadriceps femoris muscle strength (r = 0.30; p = 0.011). However, no significant correlation was found between quadriceps femoris muscle strength and Kujala scores (r = 0.22; p = 0.061). The morphology of the VMO muscle was significantly associated with the incidence of PFPS and quadriceps femoris muscle strength in athletes. These findings support the use of VMO CSA symmetry monitoring as part of early PFPS risk screening and emphasize the importance of a multisegmental approach in PFPS prevention programs for athletes.